A study in the evolution of Lancelot's knightly identity in Chrétien De Troyes' 'Le Chevalier De La Charrette' and Sir Thomas Malory's 'Le Morte Darthur' - Tay, Ariel Sok Ee (2015)
In Chrétien De Troyes’s Le Chevalier De La Charrette, identity – knightly or otherwise is ever changing. This is especially so with regard to the unnamed protagonist whom we much later learn is to be Lancelot. In Sir Thomas Malory’s Le Morte Darthur, the character of Lancelot never really loses his name unless he wilfully displaces himself. He does however struggle with his worldly desires and pursuits that distract from both his knightly and religious obligations which prevents his success in the Grael quest. Following this failure his chief struggle lies with his inability to reform his old ways to become the ‘best knight in the world’ and not just the ‘best of the worldly’.In this essay I will be looking into the various formations and inversions of identity within Chrétien De Troyes’s Le Chevalier De La Charrette and Sir Thomas Malory’s Le Morte Darthur focusing primarily on the character, Lancelot. With this I will analyse the evolution of his identity within each text and how they differ. As Neivergelt defines it, knightly identity is more a concept of progress, of movement and becoming. However, because of this definition for the ever-changing it is impossible to attach a specific string of attributes to ‘knightly identity’. That said, when Neivergelt defines it to be a state of becoming, one may yet beg to question, what are they becoming and to what are they always moving towards?